IMPLEMENTATION OF PERFORMANCE-BASED BUDGETING AS A LEGAL INSTRUMENT IN PUBLIC FINANCIAL MANAGEMENT IN INDONESIA - Ahmad, Riano Purwonegoro; Rahmat, Diding; Noverita, Lasmauli (JILPR Journal Indonesia Law and Policy Review, 2026)
The implementation of performance-based budgeting is an important part of state financial management reform, which aims to improve transparency, accountability, and efficiency in the use of public budgets. This system links the allocation of funds to measurable performance outcomes, thereby changing the paradigm of financial management from simply absorbing the budget to achieving effective and efficient results. This study discusses how performance-based budgeting functions not only as a technocratic tool but also as a legal instrument that binds government institutions to be accountable for the results of state budget use. The legal basis for PBB in Indonesia is reflected in Law No. 17 of 2003 on State Finance and Law No. 1 of 2004 on State Treasury. However, in practice, the implementation of PBB still faces various challenges, such as limited human resources, weak performance indicator development, and a lack of integration between planning and budgeting. Therefore, it is necessary to improve the capacity of civil servants, strengthen information systems, and promote synergy between institutions to encourage the creation of better, more transparent, and accountable state financial management. Thus, performance-based budgeting plays a strategic role as a legal instrument in achieving accountable and results-oriented governance.